Anáforas indiretas em produções escritas de alunos - Apergis, Jane Gasperini (2010)
This work aims to verify cases in point of indirect anaphoras and their functions in the textual coherence field in writing of students from secondary school. According to interactional socio-cognitive perspective of language, the discourse reference is a discursive activity for (Mondada & Dubois, 2003), Apothéloz & Chanet (2003), Schwarz (2007), Conte (2003), Francis (2003), Marcuschi (2000), Koch (2003, 2004), Koch & Marcuschi (1998), Cavalcante (2000, 2003, 2005), we have sought to identify cases in point of indirect anaphoras in school texts and we have sought to analyse their configuration and their contribution to form the coherence. In order to get the purpose, we have chosen a corpus of written texts of students of ninth grade from a public secondary school. The results suggest that indirect anaphoras are important mechanisms for writing because they perform several functions in the articulation of texts and they are tightening related to fields of coherence